Secure analysis of multi‐antenna cooperative networks with residual transceiver HIs and CEEs. Issue 17 (1st October 2019) - Li, Xingwang; Huang, Mengyan; Li, Jingjing; Yu, Qingping; Rabie, Khaled; Cavalcante, Charles C.
Abstract : This paper investigates the secure performance of multi‐antenna decode‐and‐forward (DF) relaying networks where the Nakagami‐ m fading channel is taken into account. In practice, the joint impact of residual transceiver hardware impairments (HIs) and channel estimation errors (CEEs) on the outage probability (OP) and intercept probability (IP) are taken into account. Considering HIs and CEEs, an optimal transmit antenna selection scheme is proposed to enhance the secure performance and then a collaborative eavesdropping scheme is proposed. More specifically, they derive exact closed‐form expressions for the outage and intercept probabilities. To obtain more useful insights the asymptotic behaviours for the OP are examined in the high signal‐to‐noise ratio (SNR) regime and the diversity orders are obtained and discussed. Simulation results confirm the analytical derivations and demonstrate that: (i) As the power distribution coefficient increases, OP decreases, while IP increases; (ii) There exist error floors for the OP at high SNRs, which is determined by CEEs; (iii) The secure performance can be improved by increasing the number of source antennas and artificial noise quantisation coefficient, while as the number of eavesdropping increases, the security of the system is reduced; (iv) There is a trade‐off between the OP and IP.